1993
DOI: 10.1037/0022-006x.61.4.611
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of applied relaxation and cognitive-behavioral therapy in the treatment of generalized anxiety disorder.

Abstract: Nondirective (ND), applied relaxation (AR), and cognitive behavioral (CBT) therapies for generalized anxiety disorder (GAD) were compared. The latter 2 conditions were generally equivalent in outcome but superior to ND at postassessment. The 3 conditions did not differ on several process measures, and ND created the greatest depth of emotional processing. Follow-up results indicated losses in gains in ND, maintained gains in the other 2 conditions, especially CBT, and highest endstate functioning for CBT. AR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
505
5
30

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 614 publications
(573 citation statements)
references
References 19 publications
21
505
5
30
Order By: Relevance
“…Moreover, comparisons with a ''psychological placebo'', a pill placebo or comparable control group conditions showed that CBT has not only unspecific psychotherapy effects, but also specific ingredients (Borkovec et al 1987;Borkovec and Costello 1993;Linden et al 2005;Power et al 1990;Stanley et al 2003). In one study, CBT for GAD was superior to a wait list, but was not more effective than a psychological placebo (Wetherell et al 2003).…”
Section: )(D)mentioning
confidence: 99%
“…Moreover, comparisons with a ''psychological placebo'', a pill placebo or comparable control group conditions showed that CBT has not only unspecific psychotherapy effects, but also specific ingredients (Borkovec et al 1987;Borkovec and Costello 1993;Linden et al 2005;Power et al 1990;Stanley et al 2003). In one study, CBT for GAD was superior to a wait list, but was not more effective than a psychological placebo (Wetherell et al 2003).…”
Section: )(D)mentioning
confidence: 99%
“…Moreover, in general, CT has demonstrated stronger long-term effects relative to other treatments. One trial, for example, reported that 58% of CT evidenced clinically significant change at 12-month follow-up, compared with 38% for applied relaxation (Borkovec & Costello, 1993). …”
Section: Generalized Anxiety Disordermentioning
confidence: 99%
“…The CEQ is self-report questionnaire which was developed for use by Borkovec and Costello (1993) and derives two factors: expectancy for change and treatment credibility (Devilly & Borkovec, 2000). These factors have been found to be stable across different populations, with high internal consistency within each factor (standardized @ ϭ 0.84 to 0.85 for the whole scale).…”
Section: Alcohol Consumption Estimate (Ace)mentioning
confidence: 99%